Meningkatkan pengetahuan dan kemampuan kader kesehatan melalui pelatihan bantuan hidup dasar - Santi Herlina; Wiwin Winarti; Chandra Tri Wahyudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2018)
Depok City has status as RW Siaga which has been upgraded to RW Siaga Aktif. So that the community, especially health cadres involved in it, are more active in preventing and managing diseases within the community. The government's efforts to reduce mortality are one of forming health cadres in each region. Health cadres have the role in assisting health workers in day-to-day health emergency response. Therefore, basic community-based life assistance training needs to be developed. The purpose of this community service activity is to increase the knowledge and skills of the Limo City Depok health cadre about providing basic life support in emergency conditions within the community so that first aid can be given before the patient taken to the hospital. The method of carrying out activities is training health cadres on basic life support and preparing the modules of basic life support which can later be the guide for health cadres. The result of this activity is that the increasing independence of the community in the health sector with the results of basic life support knowledge increased to 53%, and 80% of health cadres were able to carry out basic life support skills.